PORTRAYAL OF AUTISM IN ATYPICAL FILM: PRAGMATIC LANGUAGE IMPAIRMENT ANALYSIS - Roudhoh Nur Fatimah; Alfi Syahriyani (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
This study investigates the portrayal of the autistic character in Atypical film seasons one and two through verbal and non-verbal pragmatic language impairment analysis. The qualitative method and the theory of mind by Attwood and Stemmer Whitaker were employed in the research. This study found that the autistic character in Atypical film made 320 language impairments, including verbal and non-verbal languages. For verbal language impairment, literal interpretations and violation of maxims were frequently found, where the repetitions often occurred. Other quite significant language impairments were monologue, odd prosody, and echolalia. Besides, the idiosyncratic speech was rarely used by the character. For non-verbal pragmatic language impairment, the character mainly utilized clumsy or gauche body language, followed by limited use of gesture and facial expressions, inappropriate facial expressions, and peculiar or stiff gazes. These findings proved that the character of the series was represented as the ASD sufferer with the Asperger syndrome spectrum. Language impairment greatly affected the development of thoughts and how the character adjusted tone and intonation of speech. It was challenging to control verbal language well, so non-verbal communication was often disrupted.